Comparison Study between Borophene/Graphene and Boron-Graphdiyne in DFT using Quantum Espresso - Ramess, Visrutii; Mohd Sarif, Ahmad Hassan Sallehudin (Enhanced Knowledge in Sciences and Technology, 2025)
The global transition from fossil fuels to renewable energy sources under the decarbonization framework raises concerns about energy availability during off-peak periods. To ensure long-term energy storage, battery energy storage systems (BESS) such as sodium-ion batteries (NIBs) have gained significant research attention, particularly regarding their anode materials. This study employs first-principles Density Functional Theory (DFT) calculations using Quantum Espresso to compare the Na adsorption properties of borophene/graphene (B/G) heterostructures and boron-graphdiyne (BGDY) monolayers as potential NIB anode materials. The adsorption energies of Na at three distinct sites were computed based on the total energy of the pristine structures and Na-adsorbed configurations. For the B/G heterostructure, the adsorption energies at sites A, B, and C were 128.6418 eV, 80.2137 eV, and 0.8572 eV, respectively. Meanwhile, the BGDY monolayer exhibited adsorption energies of 2.1973 eV, 2.0681 eV, and 2.8463 eV at the corresponding sites. These values indicate weak or unfavourable Na interactions with both materials, attributed to low charge transfer, weak orbital overlap, unfavourable adsorption geometries, and unoptimized structures. Consequently, neither material is currently suitable for NIB applications without further modification. Future research should focus on structural optimization and surface modifications to achieve negative adsorption energies, enabling a more comprehensive comparison of their potential as anode materials.